Municipal Vulnerability to Climate Change and Climate-Related Events in Mexico - Borja-Vega, Christian (World Bank, Washington, DC, 2013)
A climate change vulnerability index in agriculture is presented at the municipal level in Mexico. Because the index is built with a multidimensional approach to vulnerability (exposure, sensitivity and adaptive capacity), it represents a tool for policy makers, academics and government alike to inform decisions about climate change resilience and regional variations within the country. The index entails baseline (2005) and prediction (2045) levels based on historic climate data and future-climate modeling. The results of the analysis suggest a wide variation in municipal vulnerability across the country at baseline and prediction points. The vulnerability index shows that highly vulnerable municipalities demonstrate higher climate extremes, which increases uncertainty for harvest periods, and for agricultural yields and outputs. The index shows at baseline that coastal areas host some of the most vulnerable municipalities to climate change in Mexico. However, it also shows that the Northwest and Central regions will likely experience the largest shifts in vulnerability between 2005 and 2045. Finally, vulnerability is found to vary according to specific variables: municipalities with higher vulnerability have more adverse socio-demographic conditions. With the vast municipal data available in Mexico, further sub-index estimations can lead to answers for specific policy and research questions.